INFLUENCE OF FORMULATION PARAMETERS ON DISSOLUTION RATE ENHANCEMENT OF PIROXICAM USING LIQUISOLID TECHNIQUE - Lahmo, Pemba; Singh, Sachin Kumar; Garg, Varun; Maharshi, Peddi; Yadav, Ankit Kumar; Gulati, Monica; Kumar, Bimlesh; Pandey, Narendra Kumar; Kaur, Prabhjot; Narang, Rakesh; et al. (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: This study revealed formulation of a liquisolid system of poorly soluble piroxicam to enhance its dissolution rate. To formulate a liquisolid system loaded with piroxicam, solubility study was carried out in various non-volatile liquids. Methods: In 1 ml of polyethylene glycol (PEG) 600, 100 mg piroxicam was added and stirred with gentle heating. To the above liquid medication, 1 g microcrystalline cellulose (MCC) 102 (as MCC has given better results), 1 g Syloid 244 FP, 2 g PEG 4000, 500 mg aerosil 200, and 0.255 g sodium starch glycolate (SSG) (5%) were added and mixed properly. The blend was compressed and subjected for quality control parameters. Results: Among all the non-volatile liquids evaluated, piroxicam was most soluble in PEG 600. Using this as liquid medication, several liquisolid compacts were prepared by varying the ratios of MCC PH 102 as carrier and Syloid 244FP as coating material and evaluated for precompression studies. To further accelerate the release of drug, various additives were added in the formulation. Among them, PEG 4000 has shown better flow as well as compression properties. Hence, the final formulation (LS-16B) was prepared using a combination of MCC PH 102, Syloid 244 FP, PEG 4000 and SSG as superdisintegrant. The dissolution studies revealed that about 92.18% drug got released from liquisolid compacts in 120 minutes, whereas only 68.16% release was observed for pure piroxicam. X-ray diffraction and scanning electron microscopy images revealed the successful formation of liquisolid system. Conclusion: It was concluded that dissolution rate of poorly soluble piroxicam could be enhanced using liquisolid technique. Keywords: Piroxicam, Polyethylene glycol 600, Microcrystalline cellulose PH 102, Syloid 244 FP, Polyethylene glycol 4000.